TRIP GENERATION OF ADULT WORKERS: A CASE OF GHANA - Marian Owiredua ANKOMAH; Sivaramakrishnan SRINIVASAN (Journal of Construction Project Management and Innovation)
Understanding the travel behaviour of road users is important in the development of transportation plans. In Ghana, most studies focus on mode choice modelling with truly little studies on trip generation. This paper examines the influence of household and individual characteristics together with other explanatory variables on trip generation using data from the 2012 Ghana Transport Indicator Database Survey which was conducted by the Ghana Statistical Service. Linear regression models were used to model the number of trips by car, bicycle, motorcycle, foot, taxi and bus for all working adults. The results from the study show that gender, age, education level and residential location all show a significant impact on the number of trips generated for the different trip modes.  From the results, the cultural background of a worker also significantly affect bicycle trips a worker make. Also, adult household is that reside in the city center make fewer trips by car than similar adults that live outside the city center. The number of trips generated by an adult worker can also be used to explain the perception variables estimate. The model results can also be used to make trip generation prediction in developing transportation plans for Ghana